Action Learning for Managers. - Pedler, Mike (Ashgate Pub., 2010)
Action Learning for Managers is a clear, concise and straightforward guide to this well-established approach to problem solving and learning in groups that enables change in individuals, teams, organisations and systems. Through action learning people develop themselves and build the relationships that are the key to improving operations and bringing about innovations.